Androgen levels and energy metabolism in Oreochromis mossambicus - Ros, A. F. H. (2014)
Two studies were conducted to test the relationship between androgens and routine metabolism in the Mozambique tilapia Oreochromis mossambicus. In the first study, endogenous levels of plasma levels of androgens and oxygen consumption rate were measured. In accordance with expectations routine metabolism corrected for metabolic body mass, was positively correlated with the behaviourally active metabolite of testosterone, 11-ketotestosterone, but not with testosterone itself.